SHIFT KERJA, GANGGUAN TIDUR DAN KELELAHAN KERJA PADA PERAWAT WANITA - Trisnawati, Elly (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
Nurse woman with married status that should work with the shift mechanism, will receive an additional burden in the form of physical and mental fatigue due to the disruption caused by the need for sleep. Women also have a tendency prone to fatigue. When working in a state of fatigue, workers will tend to make mistakes and the risk of accidents. The purpose of this study was to determine the relationship between shift work and sleep disorder, shift work and fatigue. And than to determine the correlation between sleep disorders and fatigue. This study uses an analytical observational study with cross sectional design. Location of the study in class III inpatient wards Hospital Dr. Soedarso Pontianak. The subjects of the study of female nurses with married status, taken by purposive sampling. Test used is the Pearson correlation and One Way Anova. The results showed that (1) there is a relationship between shift work and sleep disorder female nurses; (2) there is a difference between the levels of sleep disturbance morning shift, day shift / evening and night shift; (3) there is a relationship between shift work and fatigue in nurses working women; (4) there is a difference between the level of job burnout morning shift, day shift / evening and night shift; (5) there is a very strong relationship between sleep disorder and fatigue female nurses. It is recommended to the hospital management to rethink the distribution of working time (duration of work) on each shift to be more proportionate to the terms and continue to improve the power of K3 in the hospital environment